2018
DOI: 10.1016/j.epsl.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiple episodes of fast exhumation since Cretaceous in southeast Tibet, revealed by low-temperature thermochronology

Abstract: Multiple episodes of fast exhumation since Cretaceous in southeast Tibet, revealed by low-temperature thermochronology, Earth and Planetary Science Letters, pp 62-76, https://doi. Abstract 33The southeast margin of the Tibetan plateau is characterized by deeply incised river 34 valleys separated by a perched low relief landscape that gently descends from the high 35 Tibetan plateau towards the southeast. When and how this unique landscape formed is 36 debated. The onset of increased river incision is often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 56 publications
7
100
1
Order By: Relevance
“…Previous studies reported an Oligocene‐early Miocene phase of enhanced exhumation in the central segment of the Longmen Shan (Wang et al, ), Jiulong Shan (Zhang et al, ), and sites further to the south (Liu‐Zeng et al, ; Shen et al, ). But this phase of exhumation is not found in the Min Shan area, even though we have used a similar combination of thermochronology methods as those previous studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies reported an Oligocene‐early Miocene phase of enhanced exhumation in the central segment of the Longmen Shan (Wang et al, ), Jiulong Shan (Zhang et al, ), and sites further to the south (Liu‐Zeng et al, ; Shen et al, ). But this phase of exhumation is not found in the Min Shan area, even though we have used a similar combination of thermochronology methods as those previous studies.…”
Section: Discussionmentioning
confidence: 97%
“…First, many studies used exhumation history determined from thermochronology data as an index for surface uplift and suggested that growth of the high‐relief topography initiated at the late Miocene (5–12 Ma) in the eastern Tibetan Plateau (Clark, Bush, et al, ; Jolivet et al, ; Kirby et al, ; Ouimet et al, ; Tan et al, ), mid‐Miocene (15–22 Ma) in southeastern Tibetan Plateau (Tian, Kohn, Hu, et al, ), or at variable times in different sectors (Shen et al, ; Tian, Kohn, Hu, et al, ; Yang et al, ; Wang et al, ). It is worth noting that the multimethod thermochronology data from vertical profiles in the central Longen Shan (Wang et al, ), Jiulong Shan (Zhang et al, ), the First Bend of the Yangtze River (Shen et al, ), and Three River region (Liu‐Zeng et al, ) suggested an Oligocene‐early Miocene (~35–15 Ma) phase of exhumation, prior to the late Miocene phase. However, it remains unknown whether this earlier phase of exhumation was a regional or local event.…”
Section: Introductionmentioning
confidence: 99%
“…West of the first topographic step, in the hanging wall of the YTB, an area with a mean elevation of ~3.5 km encompasses most of the Jianchuan basin. The present‐day landscape is characterized by relict low‐relief surfaces as defined by Clark et al () and Liu‐Zeng et al () but is locally controlled by a set of normal faults bounding the Pliocene‐Quaternary Dianwei and Heqing basins (Figures , , and g–i). Between the YTB and the CHT‐JQTB, the mean elevation is ~2.7 km and the landscape is shaped by incision of the Jinsha River and normal faults bounding the Chenghai Lake.…”
Section: Structural and Morphometric Analysismentioning
confidence: 97%
“…2). In the Mekong area, Liu- Zeng et al (2018) and Yang et al (2016) combined AHe, ZHe, and apatite fission-track dating that indicate two exhumation phases ca. 60-40 Ma and ca.…”
Section: Implications On the Exhumation History Of Se Tibetmentioning
confidence: 99%
“…1). Several studies based on different techniques have constrained erosion in several locations along these rivers at the million-year time scale (Clark et al, 2005;Ouimet et al, 2010;Wilson and Fowler, 2011;Duvall et al, 2012;Tian et al, 2014;Ping et al, 2015;Zhang et al, 2015;Shen et al, 2016;Yang et al, 2016;McPhillips et al, 2016;Liu-Zeng et al, 2018;Nie et al, 2018) and at the 1-100 k.y. time scale (Henck et al, 2011;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%